2016
DOI: 10.7326/m15-2650
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Medications as Monotherapy or Metformin-Based Combination Therapy for Type 2 Diabetes

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
413
0
34

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(457 citation statements)
references
References 59 publications
10
413
0
34
Order By: Relevance
“…Although, metformin the most significant analogue of biguanides was known for its antidiabetic properties since 1959, it was not commercially available before late 90s. Metformin mechanism involves the reduce of hepatic glucose production, improve insulin sensitivity as well as peripheral glucose utilization 5,16,36,37 . Metformin use in Type 2 DM may be associated with reduced cancer mortality rates.…”
Section: Biguanidesmentioning
confidence: 99%
“…Although, metformin the most significant analogue of biguanides was known for its antidiabetic properties since 1959, it was not commercially available before late 90s. Metformin mechanism involves the reduce of hepatic glucose production, improve insulin sensitivity as well as peripheral glucose utilization 5,16,36,37 . Metformin use in Type 2 DM may be associated with reduced cancer mortality rates.…”
Section: Biguanidesmentioning
confidence: 99%
“…MET decreases blood glucose levels by decreasing hepatic glucose production, decreasing intestinal absorption of glucose, and improving insulin sensitivity by increasing peripheral glucose uptake and utilization. These effects are mediated by the initial activation by MET of AMP-activated protein kinase, a liver enzyme that plays an important role in insulin signaling, whole body energy balance, and the metabolism of glucose and fats [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, with perhaps the exception of insulin, has unsurpassed efficacy for HbA 1c reduction, typically in the 1-1.5% range, influenced to some degree by baseline glycemia (24). Whenever it has been compared head-to-head with other drugs, equivalent glycemic reductions have been measured or, in some studies, an actual advantage to metformin has been found (24). Admittedly, however, the degree of HbA 1c reduction may not necessarily be the most important outcome from a medication used for diabetes.…”
mentioning
confidence: 99%